MANAJEMEN SUMBER DAYA MANUSIA BERBASIS KOMPETENSI KERJA - Samsuni, Samsuni (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2018)
Human resources is a central and important sector within the framework of the attainment of objectives in an organization or company, because of the existence of ability skill of workers and the quality of human resources can drive the organizations or companies with good and right. Many human resources management roles in fostering good performance like the competency work. In addition, it should be noted the factors that affect human resources because it will disrupt the stability of work. Therefore it needs to be a way to resolve the matter by increasing expectations and identify obstacles. Keywords: management, human resources, work.